Advanced structural materials : selected peer reviewed papers from IUMRS-ICA 2010, 11th IUMRS International Conference in Asia, 25-28 September 2010, Qingdao, China - Han, Yafang (Materials science forum ;, 2011)
These 136 peer-reviewed papers cover the current understanding of researchers working in the fields of magnesium alloy use, structural composite materials, advanced materials processing technologies, high-temperature coatings, surface protection and aerospace materials. The result is an uniquely helpful guide to the subject. Review from Book News Inc.: One of five volumes containing the proceedings of the selected papers presented at the 11th IUMRS (International Union of Materials Research Societies) International Conference in Asia, held in Qingdao, China, in September of 2010, which brought.